Freedom, Oversight, and Sanctions in Digital Financial Services: Toward Sustainable Development Goals in Indonesia - Hamid, Abdul; Afifullah , Muhamad; Sakti, Muthia (PT. Hafasy Dwi Nawasena, 2025)
The rapid growth of digital financial services in Indonesia has reshaped financial transactions by increasing accessibility, efficiency, and innovation, thereby supporting financial inclusion and economic growth. However, this progress also presents challenges related to security, consumer protection, and regulatory adequacy. This study examines the balance between freedom and oversight in digital financial transactions and assesses the role of sanctions on service providers. Using a normative juridical approach with statutory, conceptual, and case-based analysis, the research explores how Indonesia’s legal framework addresses the dual challenge of encouraging innovation while protecting public interests. The findings show that freedom in digital finance expands inclusivity but also increases risks of cybercrime, fraud, data misuse, and instability, especially concerning digital assets. Oversight mechanisms are essential to ensure transparency, compliance, and stability. Sanctions—administrative, civil, or criminal—function as tools to compel providers to adopt stronger standards of security, accountability, and consumer protection. While sanctions may impose costs, they strengthen compliance and enhance public trust. The study concludes that balancing freedom, supervision, and sanctions is vital to creating an innovative yet accountable digital financial ecosystem. Moreover, these regulatory measures contribute to the Sustainable Development Goals (SDGs), particularly economic growth (SDG 8), innovation and infrastructure (SDG 9), reducing inequalities (SDG 10), and strong institutions (SDG 16).